Reconceptualization of Islamic Education in Indonesia: Future Strategies and Approaches - Muh Barid Nizarudin Wajdi; Siti Marpuah; ⁠Shakila Binti Ahmad Binti Ahmad; ⁠Mohd Hisyam Bin Abdul Rahim Abdul Rahim; Mikdar Rusdi (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
Islamic education in Indonesia has historically played a key role in shaping both religious and societal values. However, in the face of globalization, technological advancement, and modern societal demands, traditional Islamic educational models are under pressure to evolve. This study aims to reconceptualize Islamic education in Indonesia, exploring how it can balance the preservation of religious values with the necessity for modernization. The research employed a qualitative approach, using interviews, focus group discussions (FGDs), observations, and document analysis to gather data from a variety of Islamic educational institutions, including pesantren, madrasah, and universities. The findings revealed significant gaps in the integration of technology, a narrow curriculum that lacks modern subjects, and insufficient emphasis on critical thinking and intercultural competence. These findings highlight the need for curricular reform, greater use of digital tools, and teaching methods that promote critical engagement with both religious and secular knowledge. The study concludes that for Islamic education in Indonesia to remain relevant and impactful, it must embrace modern educational practices while preserving its core religious identity. This research advances the field by providing a strategic framework for integrating modern subjects into Islamic education, thus ensuring that students are better prepared for both religious and global societal roles. Future studies should focus on the long-term impacts of these reforms and the development of effective training programs for educators in Islamic institutions.